2012
DOI: 10.1073/pnas.1119167109
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination, localization, and stability of an anti-apoptotic BCL2-like protein, BCL2L10/BCLb, are regulated by Ubiquilin1

Abstract: We have previously shown that all six members of the anti-apoptotic BCL2 gene family can cooperate with (myelocytomatosis oncogene) MYC in a mouse model of leukemia, but three of them are significantly less potent contributors to leukemogenicity than the other three. The protein encoded by one of these less potent genes, BCL2L10∕BCLb, was recently shown to vary dramatically in many primary human cancers by immunohistochemistry, and the protein levels were inversely correlated with survival in patients with sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(105 citation statements)
references
References 43 publications
7
97
0
Order By: Relevance
“…In contrast, Bcl-2, Bcl-w, and Bcl-xL were stable, with half-lives of about 20 hours. This agrees with published data on the untagged proteins, 14,22,36,37 indicating that GFP fusion did not influence the turnover of the Bcl-2 proteins. Accordingly, the turnover of GFP-Bcl-2 and GFP-Mcl-1 was virtually identical to that of endogenous Bcl-2 and Mcl-1 in the same cells (supplemental Figure 7).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, Bcl-2, Bcl-w, and Bcl-xL were stable, with half-lives of about 20 hours. This agrees with published data on the untagged proteins, 14,22,36,37 indicating that GFP fusion did not influence the turnover of the Bcl-2 proteins. Accordingly, the turnover of GFP-Bcl-2 and GFP-Mcl-1 was virtually identical to that of endogenous Bcl-2 and Mcl-1 in the same cells (supplemental Figure 7).…”
Section: Resultssupporting
confidence: 92%
“…The dichotomy in antiapoptotic capacity of the prosurvival Bcl-2 proteins is not restricted to therapy resistance. An Em-Myc-driven leukemogenesis model revealed that Bcl-2, Bcl-xL, and Bcl-w also have a greater oncogenic potency than Bcl-B, Bfl-1, and Mcl-1, 2 whereas stabilized versions of Bcl-B 36 and Bfl-1 22 were as potent in accelerating tumorigenesis as Bcl-xL. Interestingly, a stabilized form of Mcl-1 expressed from the endogenous gene locus was recently found to largely rescue the dramatic developmental deficiencies of Bcl-2 2/2 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent expression of two HIF-1α downstream molecules, VEGF and platelet-derived growth factor (PdGF), is correlated with inferior event free-survival in osteosarcoma (19,20). With regard to malignant tumor effects related to UBQLN, it stabilizes BCL2L10/BCLb, one of the six anti-apoptotic members of the BCL2 family, inhibits apoptosis, and contributes to the survival of human lung cancer cells (9). Thus, the function of UBQLN in cancer cells is the same as that in osteosarcoma, in that it inhibits hypoxia-induced apoptosis in tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of the UBQLN2 gene suppress ubiquitin-mediated proteasomal degradation, leading to the accumulation of inclusions composed of misfolded proteins linked to the onset of ALS (8). Moreover, higher UBQLN mRNA levels are associated with shorter survival of lung cancer patients and UBQLN is an important factor in tumor progression (9).…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are encoded by genes on different chromosomes: UBQLN1 (9q22, 589 or 561 amino acids), UBQLN2 (Xp11.21, 624 amino acids), UBQLN3 (11p15, 654 amino acids), UBQLN4 (1q21, 601 amino acids) and UBQLN-L (11p15.4, 475 amino acids) [1].…”
Section: Ubiquilins (Plics)mentioning
confidence: 99%